The South American genus Protothereva Malloch (Diptera: Therevidae: Therevinae) with description of two new species - Webb, Donald W.; Metz, Mark A. (Zootaxa, 2003)
The genus Protothereva Malloch, 1932, was described based on a single female from southwestern Argentina. The genus is revised with the description of two new species, P. ecuadorensis Webb from Ecuador and P. peruensisWebb from Peru, represented by both male and female specimens. A key to the identification of the species is included along with illustrations of the genitalia and a map of the species distributions. The genus Protothereva is redefined to include the male characteristics.